Trends of middle school students in Al-Ahsa Governorate in the use of simulation technology in education - Al-Nasser, Ahmed Sami; Al-Dariwish, Ahmed Abdullah (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the trends of middle second graders toward using computer simulation technology in their computer courses. The research followed a semi-experimental curriculum. The study sample consisted of 28 students in the second intermediate grade in the governorate of Al-Ahsa in the third semester of 1442 AH / 1443 AH. The study sample was taught using simulation technology in the computer course instead of the traditional method. A five-grade Likert trend measure was prepared to achieve the study objectives. The study results showed statistically significant differences between the average of the tribal and distance measurements of the pilot group students in the trend scale for the distance measurement. Based on the results of the study, several recommendations were reached, the most prominent of which are: creating simulations of paid computer programs instead of buying them on each device; using simulation technology to explain practical lessons instead of the traditional method because of the advantages it offers, such as learning a student anytime, anywhere he wants, and will not need a teacher to teach him.
Keywords: Modeling; Spreadsheet; CNC; Skill Performance; Microsoft Excel